Cover Picture: Precisely Tailoring Upconversion Dynamics via Energy Migration in Core–Shell Nanostructures (Angew. Chem. Int. Ed. 12/2018). Issue 12 (28th February 2018) - Zuo, Jing; Sun, Dapeng; Tu, Langping; Wu, Yanni; Cao, Yinghui; Xue, Bin; Zhang, Youlin; Chang, Yulei; Liu, Xiaomin; Kong, Xianggui; Buma, Wybren Jan; Meijer, Evert Jan; et al.
Abstract : Random migration of excitation energy affects the upconversion dynamics of lanthanide‐doped nanomaterials. In their Communication onpage 3054 ff., X. G. Kong, E. J. Meijer, H. Zhang et al. illustrate the relation between upconversion dynamics and energy migration processes and demonstrate an approach to tailor the upconversion dynamics through controlling the energy migration path in nanoparticles, in which the upconversion emission is visualized as "collisions" of randomly "walking" excited states.